1995
DOI: 10.1016/0014-5793(95)00923-w
|View full text |Cite
|
Sign up to set email alerts
|

The first observation of O2 generation at real time in vivo from non‐Kupffer sinusoidal cells in perfused rat liver during acute ethanol intoxication

Abstract: Experimental procedures Animal investigationsThe study protocol was approved by the Committee on Ethics of animal experimentation of the Japan Immunoresearch Laboratories and extra care was taken to avoid animal suffering throughout the study. Male Wistar rats (Charles River, Japan) weighing 250-300 g were fed on standard laboratory animal chow and tap water ad libitum. Before operation, the rats were anaesthetized by i,p. injection of 50 mg/kg sodium pentobarbital and then were given 1000 units/kg sodium hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 6 publications
0
24
0
1
Order By: Relevance
“…In earlier studies it was suggested that the Kupffer cells and endothelial cells generated increased concentrations of ROS as a result of acute ethanol exposure [41,42], but little evidence existed for a similar response by hepatocytes. However, Nakano et al [42] recognized that significant increases in ROS occurred that could not be associated with Kupffer cells, although they associated those elevations to endothelial cells.…”
Section: Acute Ethanol and Increased Ros Production In Livermentioning
confidence: 99%
See 2 more Smart Citations
“…In earlier studies it was suggested that the Kupffer cells and endothelial cells generated increased concentrations of ROS as a result of acute ethanol exposure [41,42], but little evidence existed for a similar response by hepatocytes. However, Nakano et al [42] recognized that significant increases in ROS occurred that could not be associated with Kupffer cells, although they associated those elevations to endothelial cells.…”
Section: Acute Ethanol and Increased Ros Production In Livermentioning
confidence: 99%
“…However, Nakano et al [42] recognized that significant increases in ROS occurred that could not be associated with Kupffer cells, although they associated those elevations to endothelial cells. It is now well established that hepatocytes also generate significant levels of ROS in the presence of ethanol.…”
Section: Acute Ethanol and Increased Ros Production In Livermentioning
confidence: 99%
See 1 more Smart Citation
“…38,39 Gd 3ϩ has been shown to have no short-term effect (Ͻ3 hours) on free-radical production by liver cells exposed to oxidants. 42,43 As predicted from the selectivity of this channel, removal of Na ϩ from the bathing medium mimicked the protective effect of the NSCC blockers (Fig. 3C).…”
Section: Resultsmentioning
confidence: 99%
“…FCLA recently developed by Goto and co-workers, is a Cypridinaluciferin analogue and is characterized by emitting light at the longest wavelength (532 nm) among the CL substances known up to now [8][9][10]. Conventional photosensitized reactions of HpD were performed in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%